Warming reduces the cover and diversity of biocrust-forming mosses and lichens, and increases the physiological stress of soil microbial communities in a semi-arid Pinus halepensis plantation - Maestre, Fernando T.; Escolar, Cristina; Bardgett, Richard D.; Dungait, Jennifer A. J.; Gozalo, Beatriz; Ochoa, Victoria (Frontiers in Microbiology, 2015)
Soil communities dominated by lichens and mosses (biocrusts) play key roles in maintaining ecosystem structure and functioning in drylands worldwide. However, few studies have explicitly evaluated how climate change-induced impacts on biocrusts affect associated soil microbial communities. We report results from a field experiment conducted in a semiarid Pinus halepensis plantation, where we setup an experiment with two factors: cover of biocrusts (low [< 15%] versus high [>50%]), and warming (control versus a ~2ºC temperature increase). Warming reduced the richness and cover (~45%) of high biocrust cover areas 53 months after the onset of the experiment. This treatment did not change the ratios between the major microbial groups, as measured by phospholipid fatty acid analysis. Warming increased the physiological stress of the Gram negative bacterial community, as indicated by the cy17:0/16:1ω7 ratio. This response was modulated by the initial biocrust cover, as the increase in this ratio with warming was higher in areas with low cover. Our findings suggest that biocrusts can slow down the negative effects of warming on the physiological status of the Gram negative bacterial community. However, as warming will likely reduce the cover and diversity of biocrusts, these positive effects will be reduced under climate change.